Studi Literatur: Pengaruh Hipnosis terhadap Penurunan Kecemasan pada Pasien Kanker - Gandi Iswanto; Rini Rachmawaty; Julianus Ake (Politeknik Kesehatan Kemenkes Mamuju, 2020)
One of the most common problems among patients with cancer is anxiety and it can cause other physiological problems caused by anxiety. This literature review aimed to review the literature on the effect of hypnosis on reducing anxiety in cancer patients. The research design used was a literature review. The search for articles used several databases, including Pubmed, Google Scholar, with the keyword Hypnosis, Hypnosis in cancer patients, the effectiveness of hypnosis, hypnosis to lower reports. The type of article used was research articles. Collected articles were reselected based on inclusion criteria, namely: 1) The purpose of the article was to analyze the effect of hypnosis on reducing anxiety in cancer patients, 2) experimental and qualitative research. Exclusion Criteria, namely: 1) not a full text article, 2) Articles that use languages other than Indonesian and English. After searching based on keywords, we obtained 791 articles from the entire database used. Then the article selection was carried out, 6 articles were selected that met the inclusion criteria, 5 articles showed the effect of hypnosis on reducing anxiety in cancer patients, 1 article stated that hypnosis with 3 stages was more optimal for reducing anxiety, namely; self hypnosis, suggestion, visualization offers restraint. Based on the foregoing, it is concluded that hypnosis has an effect on reducing anxiety in cancer patients.